Exploring Parametric Concepts and Principles for Furniture and Interior Design - Sawatmongkhonkul, Klawkanlayaphon; Joneurairatana, Eakachat; Sirivesmas, Veerawat (Interiority, 2024)
This research explores the incorporation of parametric models into the algorithmic design process, specifically focusing on furniture and interior design. It presents a case of an experimental equation centred around a waffle honeycomb structure. The first part of the article reviews three decades of literature on parametric design, which comprises its background, history, theory, and essential concepts and applications. The second part investigates the parametric design process to uncover its potential for interior design applications. The combination of parametric equations with algorithms through the utilisation of multiple steps, such as conditional loops, efficiently designs intricate systems. An intricate system in parametric design comprises various input parameters, rules, mathematical algorithms, and conditional relationships that interact to generate design solutions. This approach is potentially applied in various design scenarios to respond to specific criteria and constraints, facilitating flexibility, adjustments to potential outcomes, and achieving a high level of detail in the final result. This research primarily concentrates on the identification of parametric design methodologies and the utilisation of parametric equations in crafting furniture and interior designs featuring waffle structures. Furthermore, it introduces a versatile parametric design approach that can be applied to various design tasks, highlights the evolutionary trajectory of parametric design, and offers insights into its potential impact on future design practices. The exploration of the parametric method enhances the understanding of complex design approaches in a more accessible and innovative manner with practical applicability.